Analisis Sentimen Twitter Menggunakan Algoritma Naive Bayes Pada Kasus Koperasi Simpan Pinjam Indosurya - sembiring, Ornensya; Rulfin Tiara Kiu , Elma; Nisa Meiah Ngafidin , Khairun (Applied Information Technology and Computer Science (AICOMS), 2023)
The case of KSP Indosurya has once again attracted public attention after the alleged perpetrator, who is also the founder of the cooperative, was acquitted by the Chief Judge of the West Jakarta District Court of all charges. The ruling stated that while the defendant was proven to have committed the alleged acts, they did not constitute a criminal offense but rather a civil matter. This verdict sparked widespread public reaction and became a trending topic on Indonesian Twitter. Therefore, this study was conducted to identify and classify public sentiment regarding the KSP Indosurya case using the Naïve Bayes algorithm. The results show that negative sentiment dominated, leading to the conclusion that public sentiment on Twitter in Indonesia toward the KSP Indosurya case is predominantly negative. This conclusion is based on sentiment analysis of 1,200 data points using the Naïve Bayes method.